Early ambulance initiation versus in-hospital initiation of high dose clopidogrel in ST-segment elevation myocardial infarction - Postma, Sonja; Dambrink, Jan-Henk E.; Ottervanger, Jan Paul; Gosselink, Marcel A.T.; Koopmans, Petra C.; ten Berg, Jurrien M.; Suryapranata, Harry; van ’t Hof, Arnoud W. J. (Thrombosis and Haemostasis, 2014)
Pre-hospital infarct diagnosis gives the opportunity to start anti-platelet and anti-thrombotic agents before arrival at the PCI centre. However, more evidence is necessary to demonstrate whether high dose (HD) clopidogrel (600 mg) administered in the ambulance is associated with improved initial patency of the infarct related vessel (IRV) and/or clinical outcome compared to in-hospital initiation of HD clopidogrel. From 2001 until 2009 all consecutive ST-Segment Elevation Myocardial Infarction (STEMI) patients who underwent pre-hospital diagnosis and therapy in the ambulance were prospectively included in our single-centre cohort study. We compared initial patency of the IRV and clinical outcome in patients treated from 2001 until June 2006 (in-hospital HD clopidogrel) with patients treated from July 2006 until 2009 (ambulance HD clopidogrel). A total of 2,475 patients with STEMI were registered; of these 1,110 (44.8%) received in-hospital HD clopidogrel and 1,365 (55.2%) received ambulance HD clopidogrel. Ambulance HD clopidogrel was not independently associated with initial patency (TIMI-2/3-flow pre-PCI (odds ratio: 1.18, 95% confidence interval [CI] 0.96–1.44); however, it was associated with fewer recurrent myocardial infarctions at 30 days (hazard ratio [HR]: 0.45, 95% CI 0.22–0.93) and at one year (HR: 0.45, 95% CI 0.25–0.80). No difference in TIMI 2/3 flow post-PCI, major bleeding, mortality, MACE – and the combination of mortality and recurrent myocardial infarction at 30-days and at one year was present between the two groups. In conclusion, early in-ambulance as compared to in-hospital initiation of HD clopidogrel in STEMI patients did not improve initial patency of the IRV or clinical outcome, except for a reduction of recurrent myocardial infarction. Therefore, early administration of HD clopidogrel seems to have net clinical benefit for these patients .
Keywords: Clopidogrel; initial patency; pre-hospital; STEMI